CMOS front-end electronics for radiation sensors - Rivetti, Angelo (CRC Press, Taylor & Francis Group, 2015)
CMOS: Front-End Electronics for Radiation Sensors offers a comprehensive introduction to integrated front-end electronics for radiation detectors, focusing on devices that capture individual particles or photons and are used in nuclear and high energy physics, space instrumentation, medical physics, homeland security, and related fields